Analysis of Mathematical Problem Solving Capabilities : Impact of Improve and OSBORN Learning Models on Management Education - Munifah, Munifah; Septiyani, Windi; Rahayu, Indah Tri; Ramadhani, Rahmi; Tortop, Hasan Said (Desimal: Jurnal Matematika, 2020)
Objectives The ability to solve problems is to gain knowledge and motivation in the problem solving process of students. The researcher used the IMPROVE and OSBORN learning models to improve problem solving skills. The IMPROVE and OSBORN learning models emphasize the development of optimal mathematical skills and generate new ideas in the process of problem solving. This research is used to see the impact of the IMPROVE learning model and OSBORN learning model which is better in mathematical problem solving abilities. This research uses the Quasy Experimental Design method. Hypothesis testing uses an independent sample test. The conclusion of the study is the mathematical problem solving ability of students who use the IMPROVE learning model is better than the mathematical problem solving abilities of students who use the OSBORN learning model.